Strategi inovasi pembelajaran Pendidikan Agama Islam di SMP Negeri 3 Lubuk Pakam - Miftahul Jannah; Wahyuddin Nur Nst; Mohammad Al Farabi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Islamic Religious Education at the junior secondary school level plays an important role in shaping students’ Qur’anic literacy, understanding of worship, and religious character. However, the development of digital culture requires religious learning to be carried out through more creative, participatory, and contextual strategies so that the material does not remain limited to the cognitive aspect, but is also internalized in students’ religious behavior. This study aims to analyze the planning, implementation, supporting and inhibiting factors, as well as solutions to the obstacles in implementing innovative learning strategies in Islamic Religious Education at SMP Negeri 3 Lubuk Pakam. This study used a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving the principal, Islamic Religious Education teachers, and students as informants. Data analysis was carried out through data collection, data condensation, data display, and conclusion drawing and verification. Data validity was tested through source and method triangulation. The results show that innovative learning strategies in Islamic Religious Education were implemented through the use of digital media, learning gamification, project-based learning, flipped classroom, blended learning, cooperative learning, and contextual approaches based on local culture. The implementation of these strategies gradually improved students’ learning interest, Qur’anic reading ability, understanding of worship, and the formation of morals and religious character. Supporting factors included school support, the use of digital technology, student enthusiasm, and teacher collaboration with the surrounding environment. Meanwhile, inhibiting factors included limited facilities and infrastructure, low digital literacy among some teachers, limited learning time, and the negative influence of social media. The solutions included teacher training, the use of simple digital-based learning media, strengthening collaboration between schools and parents, and implementing more creative, participatory, and contextual learning according to students’ needs in the digital era.